Mobility-Covid-19 Impact Quadrant : Quantitative Approach to Analyze Community Responses to Covid-19 Pandemic - Usman Bustaman (Jurnal Aplikasi Statistika & Komputasi Statistik, 2020)
There are two premises regarding the relationship between mobility and COVID-19, namely: (1) mobility affects the spread of COVID-19, or (2) the spread of COVID-19 affects mobility. This paper further explores both premises to analyze community responses to COVID-19 pandemic using Google Mobility Index (mobility) and the COVID-19 Spread Risk Index (risk) of Indonesia. Cross-correlogram of both indices is examined to determine optimum values called Risk Detection Time (Rdt). A scatter plot of Rdt and its correlation coefficient resulted Mobility-COVID-19 Impact Quadrant which maps the community responses into four zones based on quadrant ‘conscious–competence’ framework. The results confirmed both premises: (1) risk can be triggered by mobility in the previous few days, or (2) mobility can represent the community responses to risk information in the previous few days. Regarding the mobility restriction implemented in Indonesia, the analysis shows that the community responses leaped from Learning zone in PSBB period (15/03/2020 to 31/05/2020) to the Recovery zone in the New Normal and PPKM period (01/06/2020 to 02/07/2021). However, the policy was late responded so that the recovery target did not go as expected and brought the community into Fear and Uncertainty zone in the Emergency PPKM period (starting from 03/07/2021).